Viṣṇu-Nārāyaṇa Changing Forms and the Becoming of a Deity in Indian Religious Traditions - Schmücker, Marcus (Verlag der Österreichischen Akademie der Wissenschaften, 2024)
The contributions collected in this volume deal with the complex history of the Indian deity Viṣṇu-Nārāyana. This conception of God evolved in various traditions in India, especially in South India, during the first millennium CE. The history of this development is reconstructed here by various means, including philological exegesis, the history of ideas, and iconographic evidence.